2018
DOI: 10.3390/aerospace5030093
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ramie Fabric Chemical Treatments on the Physical Properties of Thermoset Polylactic Acid (PLA) Composites

Abstract: Ramie fabric-reinforced thermoset polylactic acid (PLA) composites were prepared by using heat pressing technology. Fabrics were treated with alkali, silane, and alkali–silane respectively, expecting an improvement of the interface between the fabric and the matrix. Scanning electron microscopy (SEM) results indicated that after alkali treatment, impurities on the fiber surface were removed and its diameter became finer. After the silane, and alkali–silane treatments, the contact angles of the ramie fibers inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This can be attributed to the fact that alkaline treatment causes roughness of the surface of the fibers, which in turn creates more avenues for more water absorption. 40,41…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to the fact that alkaline treatment causes roughness of the surface of the fibers, which in turn creates more avenues for more water absorption. 40,41…”
Section: Resultsmentioning
confidence: 99%
“…This can be attributed to the fact that alkaline treatment causes roughness of the surface of the fibers, which in turn creates more avenues for more water absorption. 40,41 The diffusion coefficients of Urena lobata fiberreinforced PP composites may be compared with those of the other natural fiber-reinforced composite materials with varying fiber loadings as presented in Table 4. It is shown that the values of diffusion coefficient of Urena lobata fiber-reinforced PP composites are in the order of 10 �5 -10 �7 mm 2 /s or 10 �11 -10 �13 m 2 /s for natural fiber-reinforced polymer composites.…”
Section: Physical Properties Of the Compositesmentioning
confidence: 99%
“…It is demonstrated that not only the fracture toughness, interfacial shear strength, tensile strength and modulus are improved by the component hybridization, nanoparticle grafting and nano-modification, but also the fire retardation and the anti-microbial performances. Moreover, the unique hollow structure of the plant fibers can provide additional benefit in structural damping, noise reduction and heat isolation compared to traditional glass or carbon fiber counterparts, behavior that is exactly desired for an aircraft interior structure [5][6][7][8]. Additionally, in the improvement of pure natural fiber reinforced polymer properties, the utilization of valuable recycled carbon fibers (rCF) as alternatives to enhancing the properties of eco-composites has been considered.…”
Section: The Eco-compass Eu-china Projectmentioning
confidence: 99%
“…The numerical results highlight the prospect of conductive CNT networks to be used as a localized structural health monitoring technique in carbon fibre reinforced polymers (CFRP) and bio-composites. Wang et al [6] studied the effect of ramie fabric chemical treatments on the physical properties of thermoset polylactic acid (PLA) composites. It was found that chemical treatments lead to an increase in tensile and flexural strength of PLA composites while they lead to a decrease in water absorption.…”
mentioning
confidence: 99%